2011
DOI: 10.1089/jwh.2011.2788
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation in Midlife Women with Intimate Partner Violence Histories

Abstract: Background: Lifetime occurrence of intimate partner violence (IPV) in women has been associated with increased prevalence of aging-related chronic diseases, including those with a pathophysiology involving inflammation. To begin to identify potential biologic mediators of this relationship, this cross-sectional study examined associations between past IPV and circulating levels of C-reactive protein (CRP) and interleukin-6 (IL-6)-measures linked with emergence of aging-related diseases-along with in vitro IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 52 publications
3
52
0
Order By: Relevance
“…13 In addition, IPV has been linked to chronic pain, 14 chronic fear and stress states, 15 postpartum depression, 16 substance use, 17,18 cardiovascular disease and hypertension, 19 as well as chronic inflammation 20 and accelerated telomeric attrition. 6 Clearly, the trauma of IPV thus extends well beyond the acutely abusive experience and the provision of traumainformed care to affected individuals is crucial to reducing its impact.…”
Section: Ipv and Healthmentioning
confidence: 99%
“…13 In addition, IPV has been linked to chronic pain, 14 chronic fear and stress states, 15 postpartum depression, 16 substance use, 17,18 cardiovascular disease and hypertension, 19 as well as chronic inflammation 20 and accelerated telomeric attrition. 6 Clearly, the trauma of IPV thus extends well beyond the acutely abusive experience and the provision of traumainformed care to affected individuals is crucial to reducing its impact.…”
Section: Ipv and Healthmentioning
confidence: 99%
“…7 Posttraumatic stress disorder (PTSD) and depression-comorbidities associated with intimate partner violence-can also contribute to immune suppression, proinflammatory responses, and faster progression to AIDS. [41][42][43] Priority scientific research questions identified by the participants included the following: The influence of sex and age-related anatomic characteristics on HIV transmission, acquisition, and pathogenesis UNAIDS estimates that 40% of new adult infections each year are among those 15 to 24 years of age. 44 Of all young people living with HIV-some five million-75% are in subSaharan Africa 45 and 71% of these are female (Table 1).…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Physically healthy women with histories of divorce or separation were recruited from the community as part of a broader investigation of recovery from intimate partner violence (IPV) and inflammation at midlife (Newton et al, 2011). A phone interview assessed inclusion criteria (history of divorce; 45 to 60 years of age; post-menopausal defined as cessation of menses for ≥ 12 months), and exclusion criteria (no English language skills; ongoing divorce-related legal issues; psychiatric hospitalization in the preceding 6 months; active suicidal ideation; current IPV—i.e., IPV involving an ex-partner in the preceding year, or any IPV history with a current partner, defined by a score ≥ 1 on the Slapped, Threatened and Throw screener (Paranjape, Rask, & Liebschutz, 2006); chronic disease other than unmedicated hypertension; use of prescription or over-the-counter medications with inflammatory effects (including psychotropics and botanicals); blood or needle phobia; use of street drugs; current alcohol use disorder defined as ≥ 5 on the Alcohol Use Disorders Identification Test consumption questions (Dawson, Grant, Stinson, & Zhou, 2005)).…”
Section: Methodsmentioning
confidence: 99%
“…Related reports from this database have been published (Fernandez-Botran, Miller, Burns, & Newton, 2011; Newton et al, 2013; Newton et al, 2011). This research was supported by funding from the National Institute on Aging, and by a Research on Women grant from the University of Louisville.…”
mentioning
confidence: 99%